Codelivery of salinomycin and doxorubicin using nanoliposomes for targeting both liver cancer cells and cancer stem cells. (October 2016) - Gong, Zhirong; Chen, Dazhong; Xie, Fangyuan; Liu, Junjie; Zhang, He; Zou, Hao; Yu, Yuan; Chen, Yan; Sun, Zhiguo; Wang, Xinxia; Zhang, Hai; Zhang, Guoqing; et al.
Aim: To develop salinomycin-loaded nanoliposomes (SLN), doxorubicin-loaded nanoliposomes (DLN) and nanoliposomes codelivering salinomycin and doxorubicin (SDLN) to target both liver cancer cells and cancer stem cells.Materials & methods: The characterization and antitumor activity of SLN, DLN and SDLN were evaluated.Results & conclusion: The doxorubicin/salinomycin sodium mole ratio of 1:1 had the best synergistic combination index value, and was chosen as the drug ratio in SDLN. SDLN could maintain the drug ratio between 1:1 and 3:1 in 12 h in vivo . SDLN and SLN + DLN showed the best tumor inhibitory rate, and could significantly decrease the percentage of liver cancer stem cells in vivo . SDLN and SLN + DLN may serve as an effective approach to treat liver cancer.